Trade Openness, Inequality and Poverty in Latin American Countries - Bayar, Yilmaz; Sezgin, H. Funda (Ekonomika, 2017)
Globalization has quickened, especially during the past three decades, due to technological, institutional, legal and political developments in the world. During this process, many countries reduced or removed the barriers on the cross-country flows of goods, services and capital, and the global trade volume increased substantially. Therefore, openness-oriented policies have led many social and economic implications for the national economies. In this regard, this study investigates the interaction among trade openness, poverty alleviation and inequality in 11 Latin American countries by employing a panel data analysis. We revealed that trade openness and financial development affected inequality and poverty negatively in the long term, while inequality affected poverty positively.
Keywords: trade openness; financial development; poverty; income inequality; Latin American countries